Teaching of ethics in medical undergraduate programs - Alvares Lavigne de Lemos Tavares, Ana Carolina; Alvares Travassos, Ana Gabriela; da Silveira Tavares, Rodrigo; Melo Pojal da Silva Rêgo, Maria Francisca; Lopes Nunes, Rui Manuel (Acta Bioethica, 2021)
Literature points to the existent diversity in medical graduate courses’ curriculums, reinforcing the need to systematise and deepen more studies in this area with the aim of qualifying the formation of our future professionals. This study aims to understand the methods used in the teaching of Bioethics in medical graduation worldwide. It was characterised as an integrative review and the databases used were Pubmed, Scopus and Web of Science. In total 2993 articles were identified and 72 met the pre-selected criteria and were included in the review. The characteristics of teaching bioethics that stood out the most in the analysis were: teaching still very heterogeneous between different universities, use of various methodologies in the process of teaching/learning, teaching disconnected from the medical practice of students showing the need to integrate the curriculum with clinical practice and challenges of teaching-learning process. Most of the studies in this review lead us to understand that there is still no minimum parameters on the ideal method to teach bioethics, suggesting that it may affect the feeling of unpreparedness felt by students in face of ethical issues in clinical practice, despite the theoretical basis acquired.